Murky shooting: The use of auditory (non-speech) feedback on mobile audiogames - Cordeiro, J.; Baltazar, A.; Barbosa, A. (ACM International Conference Proceeding Series, 2012)

NIME education at the school of arts of the portuguese catholic university/CITAR - Martins, L.G.; Barbosa, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

The creative industries as an integrated factor in a sustainable model for Macao's economic development - Azevedo, Margarida; Barbosa, Álvaro (Creative Industries Journal, 2014)
This article presents an insight into one of the regions with the fastest-growing economy, heavily based on an entertainment, gaming and tourism industry, and that is urgently looking for a sustainable model that articulates with complementary sectors within the cultural and creative industries – Macao. Macao is facing a major economic and social challenge; it has grown as a vulnerable economy relying almost exclusively on gaming revenues. Alternative activities to diversify the economy are urgently required to answer the competition risks haunting this industry. The cultural and creative industries could be a complementary activity – a vehicle for economic diversification. However, current public and private stakeholders for the cultural and creative sector might have been neglecting the unique cultural and heritage ecosystem of the territory, focusing on isolate opportunities and overlooking an inclusive and robust strategy. A sustainable model that attends to the local conditions and its people is required for alternative activities to become a meaningful sector for the social and economic development of Macao.

Privacy in sound-based social networks - Cordeiro, J.; Barbosa, A. (Communications in Computer and Information Science, 2014)

An eco-structuralism approach in soundscape (data) composition - Gomes, J.A.; Barbosa, A.; Penha, R. (ACM International Conference Proceeding Series, 2014)

Capture and transformation of urban soundscape data for artistic creation - Gomes, Jose Alberto; Pinho, Nuno Peixoto De; Lopes, Filipe; Costa, Gustavo; Dias, Rui; Tudela, Diogo; Barbosa, Álvaro (Journal of Science and Technology of the Arts, 2014)

User Preference on Artificial Reverberation and Delay Time Parameters - Pestana, Pedro Duarte; Reiss, Joshua; Barbosa, Álvaro (Journal of the Audio Engineering Society, 2017)

The Film Sound Analysis Framework: A Conceptual tool to Interpret the Cinematic Experience - Barbosa, Álvaro; Dizon, Kristine (Journal of Science and Technology of the Arts, 2020)
Keywords: Analysis framework; Film studies; Sound and music design

Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students - Caires, C. S.; Barbosa, A.; Hanyou, W. (International Journal of Educational and Pedagogical Sciences, 2020)
Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students

Multimodal Game Design Framework for Creativity in Macau's Educational System Through Digital and Tangible Games: Chinese, Portuguese, and English Languages - Martins de Abreu, F.; Barbosa, Álvaro Mendes (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
Creativity and collaboration are crucial to learning development in today's fast-paced educational environment. New technology can bridge humans and their natural needs through immersion in digital environments with physical objects. As knowledge and information evolve, digital interactive experienc...

Static recording apparatus for soundscape analysis in Macau - Estadieu, Gerald; Cheung, Yin Yan; Pestana, Pedro Duarte; Barbosa, Alvaro (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2023)
The concept of Soundscape was initially proposed to study the relationship between humans and their sonic environment. It has gathered momentum from academia to environmentalists and policymakers throughout the years. The study and characterisation of Soundscapes can be complex as it tries to take a holistic and qualitative approach rather than simply quantifying sound pressure levels. This paper introduces a comprehensive Soundscape study process in an ongoing research project in Macao (China), a small territory (32.9 km2) and one of the most densely populated areas in the world. The paper seeks to show a first version of a technical solution to systematically capture the local soundscape, analyse it, classify it, and ultimately deliver a dataset library and the intangible qualities of the environmental sound. This implementation, including technical documentation, code, and sound library with strong labelling, is presented under an open-source license to encourage future collaborative research. Finally, the paper offers suggestions on further developing the apparatus to reach a systematic and near real-time soundscape analysis with the development of a machine learning system.